Carcinoid tumor of the appendix: A consecutive series from 1237 appendectomies - Tchana-Sato, Vincent (Baishideng Publishing Group Co., Limited, 2006)
AIM: To report the experience of the CHU Sart Tilman, University of Liège, Belgium, in the management of appendiceal carcinoid tumor. METHODS: A retrospective review of 1237 appendectomies performed in one single centre from January 2000 to May 2004, was undertaken. Analysis of demographic data, clinical presentation, histopathology, operative reports and outcome was presented. RESULTS: Among the 1237 appendectomies, 5 appendiceal carcinoid tumors were identified (0.4%) in 4 male and 1 female patients, with a mean age of 29.2 years (range: 6-82 years). Acute appendicitis was the clinical presentation for all patients. Four patients underwent open appendectomy and one a laparoscopic procedure. One patient was reoperated to complete the excision of mesoappendix. All tumors were located at the tip of the appendix with a mean diameter of 0.6 cm (range: 0.3-1.0 cm). No adjuvant therapy was performed. All patients were alive and disease-free during a mean follow-up of 33 mo. CONCLUSION: Appendiceal carcinoid tumor most often presents as appendicitis. In most cases, it is found incidentally during appendectomies and its diagnosis is rarely suspected before histological examination. Appendiceal carcinoid tumor can be managed by simple appendectomy and resection of the mesoappendix, if its size is ≤ 1 cm.